Analisis Penatalaksanaan Petugas Kesehatan Balita Diare Di Puskesmas Lanjas Muara Teweh Kabupaten Barito Utara Tahun 2016 - Achmad Rizal (Jurnal Kesehatan Indonesia, 2017)
Total morbidity of diarrhea in children under five has increased each years. In Puskesmas Lanjas Kabupaten Barito Utara in 2011 there were 272 cases (69.6 %) diarrhea of toddler, in 2012 there wan an increasing to 312 cases (77.2 %), and in 2013 there was an significant increasing to 153 cases (110.8 %) exceeding the target of 138 %. The aimed of this research was to analyze the knowledge and attitudes of health workers in the management of diarrhea in toddler through analytical survey research in order to analyze the relationship between variables which are cross-sectional study in collected data in September 2016. The sample used are 30 respondents. The collection of the data used the form of interviews those were questionnaires and analysis used to distribute the independent and dependent variables. Analysis of the statistical tests used to learn the overall relationship with the Chi Square test. From this study showed the category less of knowledge and less of management health worker were 14 health workers (87,5% ). Attitude towards management of health workers of diarrhea in toddler less the most is 11 officers (73,3.%). There was correlation between knowledge and management of diarrhea in toddler (p=0,009) and there was no correlation between attitude and management of diarrhea in toddler (p=0,635). It was needed to increase the skills of health worker in the management of diarrhea in toddler so that the health worker was able to apply the treatment of diarrhea and can disseminate standards on the management of health workers to all who served in Puskesmas lanjas even household level as efforts to reduce morbidity and prevent mortality due to diarrhea